Lesão Medular e suas significações para a família - Barbosa, Islene Victor (2008)
Spinal cord injury represents great problem in public health, which affects physically the body, leading to paraplegia or tetraplegia, bringing consequences that modify family’s dynamics, which determine a new life style to its members. This context takes family to organize itself and to reconfigure its shapes, in search for understanding the individual and learning how to live with the injury implications. We aimed, in this study, to understand the meaning of caring given by the family to a person with spinal cord injury; to find out the feelings that surround the care relationship of the spinal cord injury person’s family based on the considerations of Jean Watson’s Theory; and to analyze the family attitudes face to caring process. This study is a descriptive type, with a qualitative approach, developed at an institution reference on trauma assistance, settled on Fortaleza-CE. Seven family caregivers participated to this study. The data were collected in September to October 2007, by a semi-structured interview. The speeches were analyzed using the content analysis method. We interpreted and inferred the information supported by Jean Watson’s Transpersonal Caring Theory. We concluded that the caring meaning for the family member’s perception is expressed by difficulties related to knowledge deficit, to the fact of caring is supposed to be an exhaustive activity and to the resignation of the new role of caregiver. About the feelings aroused in response to this neurological lesion, highlighted affection, faith, sadness, anxiety and fear, preoccupation and hope. As attitudes patterns face to caring process, we pointed the aspects linked to responsibility, resignation, non-acceptance and attitudes ambivalence. Thus, we realized that it is also necessary to focus Nursing care on the family of those people affected by spinal cord injury.